The imagined pandemic: : conspiracy negationist knowledge produced in the covid-19 pandemic (Raíces: Revista de Ciencias Sociales y Políticas, 2023)
This research explains the knowledge created by various subjects who deny relevant aspects or the entirety of the current coronavirus pandemic. Its study is of vital importance to understand part of the current conflict since it makes visible a contest for the legitimacy of various discourses. This means that the negationist discourse is part of a knowledge system that includes conspiracy theories (CT), which are in dispute with the official-scientific discourses; From the ethnographic exploration it was possible to show how there is a contest of truths between these two poles. The base is based on the research carried out on the Facebook platform as a starting point for the study of conspiracy groups; From them I was able to obtain various transnational interviews and in the process I had the opportunity to extend the investigation towards the practices of conspiratorial denial narratives, since these materialize in the form of protests that are carried out monthly in Mexico City. Ethnography provided multiple knowledge since these social agents allowed me to see that this type of knowledge is not exclusive to subjects belonging to internet groups or groups of protesters, but rather it turned out to be made by “common” people who consume this knowledge. The research tries to shed light on the reasons that drive them to mistrust hegemonic discourses and promote theirs of an alternate nature where mythical imaginaries are the basis that sustains their discourse
Keywords: Conspiracy; denial; imaginary; knowledge; coronavirus